(untitled) (Philological Studies, 2019)
Andrej Stojanov is the author of the great travel literature on Tetovo and the Tetovo area, titled Notes on My Travel in the TetovoArea (Бøлøжки по п’туванието ми изъ Тетовско), published as a series in the daily newspaper “Novini” („Новини“) 1891/92. This work was certainly one of the most important travel literature works about Macedonia in the 19th century, if not the most important one, taking into consideration its length, serialization, as well as the variety of information it included on geography, toponymy, public customs, ethnography, etc. On that note, this text analyzes Stojanov’s travel literature work, as published in the newspaper “Novini” for more than a year.